A History of Spanish Golden Age Drama - Ziomek, Henryk (Book collections on Project MUSE., 1984)
Spain's Golden Age, the seventeenth century, left the world one great legacy, the flower of its dramatic genius -- the comedia. The work of the Golden Age playwrights represents the largest combined body of dramatic literature from a single historical period, comparable in magnitude to classical tragedy and comedy, to Elizabethan drama, and to French neoclassical theater. A History of Spanish Golden Age Drama is the first up-to-date survey of the history of the comedia, with special emphasis on critical approaches developed during the past ten years. A history of the comedia necessarily focuses.